ChemInform Abstract: Branch‐Selective Allylic C—H Carboxylation of Terminal Alkenes by Pd/sox Catalyst. Issue 7 (29th January 2015) - Kondo, Hiroki; Yu, Feng; Yamaguchi, Junichiro; Liu, Guosheng; Itami, Kenichiro
Abstract An allylic C—H carboxylation in presence of palladium diacetate catalyst with sulfoxide‐oxazoline ligand and benzoquinone as oxidant furnishes the corresponding branched allylic esters with high regioselectivity.